Les élections de 2018 au Québec : un « moment populiste » ? - Jean Bernatchez (IdeAs)
The 2018 elections in Quebec marked a breakthrough. After fifty years of alternating power between the centre-right Parti Libéral and the centre-left Parti Québécois, the Coalition Avenir Québec, a right-wing party founded in 2011, is called upon to form a majority government. Another highlight of this election was the success of a left-wing party founded in 2006, Québec solidaire, a product of a union of progressive forces. This party is at odds with neoliberalism and dares to make bold proposals, particularly with regard to environmental protection. The Coalition Avenir Québec embodies right-wing populism and Québec solidaire, left-wing populism, populism as an anti-establishment discursive strategy. Also, considering the political theory of realignments, these elections mark a rupture and could also constitute a “populist moment” likely to crystallize into a new electoral order. In this article, we present a summary of a historical account of the Québec elections since 1867, the year Québec was founded, organized according to five major periods, each associated with an image that illustrates the dominant frame of reference. These periods are characterized by the sequence of rupture, realignment and ordinary politics. We then propose conceptual clarifications regarding populism. Finally, we present our analysis of the 2018 Québec elections, assessed from a populist perspective.